Unraveling viscosity effects on the hysteresis losses of magnetic nanocubes. Issue 16 (11th April 2017) - Cabrera, D.; Lak, A.; Yoshida, T.; Materia, M. E.; Ortega, D.; Ludwig, F.; Guardia, P.; Sathya, A.; Pellegrino, T.; Teran, F. J.
Abstract : Viscosity may have strong variations of the dynamical magnetic response of magnetic nanoparticles. We assess the extrinsic and intrinsic parameters that strongly influence viscosity effects. Abstract : Hysteresis losses in magnetic nanoparticles constitute the basis of magnetic hyperthermia for delivering a local thermal stress. Nevertheless, this therapeutic modality is only to be realised through a careful appraisal of the best possible intrinsic and extrinsic conditions to the nanoparticles for which they maximise and preserve their heating capabilities. Low frequency (100 kHz) hysteresis loops accurately probe the dynamical magnetic response of magnetic nanoparticles in a more reliable manner than calorimetry measurements, providing conclusive quantitative data under different experimental conditions. We consider here a set of iron oxide or cobalt ferrite nanocubes of different sizes, through which we experimentally and theoretically study the influence of the viscosity of the medium on the low frequency hysteresis loops of magnetic colloids, and hence their ability to produce and dissipate heat to the surroundings. We analyse the role of nanoparticle size, size distribution, chemical composition, and field intensity in making the magnetisation dynamics sensitive to viscosity. Numerical simulations using the stochastic Landau–Lifshitz–Gilbert equation model the experimental observations in excellent agreement. These results represent an important contribution towards predicting viscosity effects and hence to maximise heat dissipation from magnetic nanoparticles regardless of the environment.